Effect of Vortex Generator on the Air-Side Thermal-Hydraulic Performance of Flat Tube Heat Exchangers - Ahmed Yousif Adam, Mohammed; A. N., Oumer; Azri, Alias; M., Ishak (Universiti Malaysia Pahang, 2016)
In the current work, the thermal-hydraulic performance of fin and flat tube heat exchangers with and without the addition of vortex generators are experimentally investigated in a relatively low Reynolds number flow. For the experimental data collection, the existing wind tunnel available at the Faculty of Mechanical Engineering (FKM) is used. However, the fins are modified by attaching triangular vortex generators of 9 mm x 9 mm size oriented at 45o to the incoming air flow direction. The fan speed is controlled so that the air flows over the fin-and-tube banks at five different air velocities (1.8 m/s, 2.3 m/s, 2.8 m/s, 3.3 m/s and 3.8 m/s) for both inline and staggered tube configurations. The obtained results show that the temperature distribution increased by a maximum of 26.9% for staggered arrangement when the vortex generator is added compared to that obtained without vortex generator. Moreover, the average heat transfer coefficient of the staggered arrangement with vortex generator is up to 46% higher than the case without vortex generator while the pressure drop for an inline arrangement with vortex generator increased up to 35% compared to the inline arrangement without vortex generator. In general, it is observed from the experimental results that the fin-and-flat tube banks with vortex generator have similar heat transfer performance and pressure drop for both arrangements. Hence, the results obtained from this study can provide information for further investigation of flat tube heat exchangers for industrial applications.